IMPROVEMENT STRATEGY OF DRUG MANAGEMENT AT PHARMACY INSTALLATION OF HARAPAN INSAN SENDAWAR HOSPITAL BY REVIEWING SUPPORTING MANAGEMENT THROUGH SWOT APPROACH - Al-Mubarak, AgustiQori; Rahmawati, Ismi; Oetari, Oetari (Jurnal Farmasi Sains dan Praktis, 2025)
Optimal drug management and drug inventory control can minimize costs and the number of orders in the next planning period. The purpose of this study was to evaluate drug management in the Pharmacy Installation of Harapan Insan Sendawar Hospital with SWOT analysis improvement strategies. The research design was descriptive based on retrospective and concurrent data. All quantitative data were compared with the indicators of The Department of Health (2008), WHO (1993), Minister of Health Regulation (2013), and Pudjaningsih in Satibi (2022). Furthermore, qualitative analysis was carried out with a SWOT approach as an alternative improvement strategy in the Pharmacy Installation based on quantitative data output and internal capital and external influences. The results of the study that meet the standards are: the level of drug availability (15,6 months) and the average prescription service time (non-compounded prescription 23,37 minutes & prescription 39,8 minutes). Results that did not meet the standard were: percentage of stock card matches with drugs (94,73%), inventory turnover ratio (2,22 times), percentage of expired drugs (4,7%), percentage of dead stock (8,97%), number of drug items per prescription sheet (3,57 items), percentage of generic drug prescriptions (76,25%). SWOT analysis of the pharmacy installation falls within the first quadrant, namely focusing on development, improving services and establishing cooperation. The conclusion drawn is that pharmacy installations can adopt aggressive strategies by enhancing the development of management information systems to optimize inventory control.